An application of an environmentally extended input-output model to the assessment of CO2 emissions of Croatian economic sectors - Davor Mikulić; Katerina Fotova Čiković; Damira Keček (Croatian Operational Research Review)
The adverse effects of pollution and the impacts of different productive sectors on the degradation of the environment have become important issues in economic development analysis. This study aims to estimate the overall carbon footprint of different economic sectors of the Croatian economy. Total CO2 emissions are decomposed by direct and indirect emissions of productive sectors and final demand by applying the environmentally extended input-output analysis (EEIO). EEIO approach enables the decomposition of the total CO2 emissions of specific sectors into emissions related to the production of final goods and services and the production of intermediate inputs delivered to other economic sectors. The highest level of direct emissions has been generated by sectors producing energy products and transportation. As the output of those sectors is required as intermediate inputs used by the other sectors, the EEIO model redistributes emissions to other sectors, delivering final products to domestic users and abroad. Besides transport and electricity, Croatia's highest level of total direct and indirect emissions is found in the construction sector, production of non-metallic mineral products and food industry.